Energy Saving Education in Villages to Support National Energy Stability and Stability of Household Expenditures - Hazmi, Muhammad; Risdwiyanto, Andriya; Jemadi, Jemadi; Dwiyanto, Bambang Sugeng; Wijono, Djoko (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract Mojogemi Village is one of the villages in Sukowono District, Jember Regency, East Java. Geographically, Mojogemi Village is very strategically located in the middle of Jember Regency. The population in Mojogemi Village is around 3,500 residents. When discussing with the Village Head and Mojogemi Village officials, Sukowono District, they encountered a number of problems regarding the wasteful use of electrical energy in the village that the people of Mojogemi Village, Sukowono District are currently facing. The problem in question is the lack of information regarding Energy Saving Education in Villages to Support National Energy Stability and Household Expenditure Stability in Mojogemi Village, Sukowono District, Jember Regency, East Java. To overcome this problem, an alternative solution that can be applied is for the author to discuss with village officials and suggest the use of alternatives to save electrical energy at this time to be able to overcome Energy Stability and Household Expenditure Stability in Mojogemi Village, Sukowono District, Jember Regency, East Java, so that Mojogemi Village can become a Villages that save energy, especially electrical energy, can stabilize energy and stabilize village household expenses and become environmentally friendly. Therefore, the aim of this community service is to see the potential for energy stability and household expenditure stability in the village in improving community welfare by saving electrical energy in Mojogemi Village, Sukowono District, Jember Regency, East Java. To obtain the data used were observation and literature study. This service activity is an educational effort to increase Energy Saving Education in Villages to Support National Energy Stability and Household Expenditure Stability in Mojogemi Village, Sukowono District, Jember Regency, East Java. As a manifestation of the author's thoughts, there are several efforts and breakthroughs offered, namely providing education on the use of energy saving to overcome the waste of electrical energy in Mojogemi Village, Sukowono District, Jember Regency, East Java so that it can support National Energy Stability and Household Expenditure Stability and become a solution for village communities. Mojogemi has its right as a citizen to obtain economical and environmentally friendly electrical energy. Keywords : Mojogemi Village, Electric Energy, Energy Saving